1979
DOI: 10.1099/00221287-114-2-443
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reducing and Other Agents on the Motility of Treponema pallidum in an Acellular Culture Medium

Abstract: 443The maintenance of Treponema pallidum motility was investigated in an acellular medium based on T. pallidurn immobilization test medium. The acellular medium contained cysteine, glutathione, thioglycollate and dithiothreitol as reducing agents and had a redox potential of -275 & 25 mV at pH 7.3. In an atmosphere containing 3 % 02, motile treponemes survived four times longer when calf serum and bovine serum albumin were added to the medium. The selective omission of glutathione and, particularly, thioglycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Their system utilized a combination of several important elements which had been previously investigated in their own laboratory and by others, including (i) monolayer cultures of a slow-growing mammalian cell line, SflEp cottontail rabbit epithelial cells (6, 10, 14); (ii) a modified tissue culture medium with 20% fetal bovine serum (FBS) and 0.63 mM dithiothreitol (DTT) to reduce oxygen toxicity (2,6,8,9,12); (iii) a small quantity (1/30th of the total medium volume) of infected testes extract ( 6) and (iv) incubation at 33°C under a microaerobic atmosphere containing 1.5% oxygen (1, 3,6,12,13). Because of the importance of this finding for future T. pallidum research and past failures in repeating reported cultivations, the techniques of Fieldsteel et al were duplicated in an attempt to independently corroborate their results.…”
mentioning
confidence: 99%
“…Their system utilized a combination of several important elements which had been previously investigated in their own laboratory and by others, including (i) monolayer cultures of a slow-growing mammalian cell line, SflEp cottontail rabbit epithelial cells (6, 10, 14); (ii) a modified tissue culture medium with 20% fetal bovine serum (FBS) and 0.63 mM dithiothreitol (DTT) to reduce oxygen toxicity (2,6,8,9,12); (iii) a small quantity (1/30th of the total medium volume) of infected testes extract ( 6) and (iv) incubation at 33°C under a microaerobic atmosphere containing 1.5% oxygen (1, 3,6,12,13). Because of the importance of this finding for future T. pallidum research and past failures in repeating reported cultivations, the techniques of Fieldsteel et al were duplicated in an attempt to independently corroborate their results.…”
mentioning
confidence: 99%
“…In low concentrations DTT appeared to be nontoxic to various rumen bacteria [3] and Treponema pallidum [12,13]. In low concentrations DTT appeared to be nontoxic to various rumen bacteria [3] and Treponema pallidum [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…In the latter experiments the percentages of motile [Chalmers and Taylor-Robinson, 1979 ;Cover et ah, 1982 ;Steiner et ah, 1981] and virulent [Steiner et ah, 1981] treponemes show a gradual decrease on prolonged in vitro storage. It seems reasonable to expect a similar decay of virulent treponemes in arti ficially infected stored donor blood.…”
Section: Discussionmentioning
confidence: 99%